Phytonutrients of bilberry fruit and saskatoon berry in the prevention and treatment of dyslipidemia - Jana Kopčeková; Jana Mrázová (National Institute of Public Health - National Institute of Hygiene, 2022)
The epidemiologic studies from the recent years indicate that high consumption of foods rich in bioactive compounds has a positive effect on human health and could diminish the risk of numerous diseases, such as cancer, heart disease, stroke, Alzheimer's disease, diabetes, cataracts, and even diseases related to age. From all species of fruit, definitely consumption of berries due to its high content of bioactive constituents prevents the risk of cardiovascular disease, oxidative stress and diabetes. The primary phenolic compounds in berries are flavonoids, particularly the anthocyanins. They have potential preventative and therapeutic effects on many diseases such as cancers, inflammation and cardiovascular diseases, obesity, neurodegenerative pathologies, and muscular degeneration. Bilberry fruits have been an important part of local diets in many countries, including Slovakia. They are valued for their pleasant taste and aroma and are often processed into jams, preserves, juices, and alcoholic beverages. In the last two decades, the Saskatoon berry has been cultivated in many parts of the world for its suitability for various food products and due to its high content of nutrients and polyphenols. Cardiovascular disease (CVD) remains the world's leading cause of morbidity and mortality. Dyslipidemia, which results from one or more abnormalities of blood lipids metabolism, remains a major key factor for progression of CVD and leads to the development of atherosclerotic plaques. The aim of this review is to compare and summarize the research evidence on the potential of bilberries and saskatoon berries with an emphasis on recent studies in humans in improving cardiovascular risk factors especially dyslipidemia.